2006
DOI: 10.1242/jcs.02795
|View full text |Cite
|
Sign up to set email alerts
|

The pH of the digestive vacuole ofPlasmodium falciparumis not associated with chloroquine resistance

Abstract: noted that this hypothesis is Chloroquine resistance in the human malaria parasite, Plasmodium falciparum, arises from decreased accumulation of the drug in the 'digestive vacuole' of the parasite, an acidic compartment in which chloroquine exerts its primary toxic effect. It has been proposed that changes in the pH of the digestive vacuole might underlie the decreased accumulation of chloroquine by chloroquineresistant parasites. In this study we have investigated the digestive vacuole pH of a chloroquine-sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
134
3
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(152 citation statements)
references
References 79 publications
(143 reference statements)
13
134
3
1
Order By: Relevance
“…Hydropathy values of amino acid side chains within a standardized synthetic polypeptide structure were determined at pH 5.0 by Kovacs et al (39). This pH value is within the measured pH range for the P. falciparum DV lumen (5,28), where the PfCRT position 76 amino acid is predicted to face (Fig. 2) (43).…”
Section: I-369fsupporting
confidence: 81%
“…Hydropathy values of amino acid side chains within a standardized synthetic polypeptide structure were determined at pH 5.0 by Kovacs et al (39). This pH value is within the measured pH range for the P. falciparum DV lumen (5,28), where the PfCRT position 76 amino acid is predicted to face (Fig. 2) (43).…”
Section: I-369fsupporting
confidence: 81%
“…A separate study however, reported a slight alkalinization of CQR parasite DVs compared with CQS parasites, although this difference disappeared at lower pHsensitive dye concentrations [33]. These discrepancies in reported DV pH may be more reflective of differences in measurement techniques than of physiological variations in parasites.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, CQR parasites may have a more acidic DV pH [20]; this finding however has been debated [11,19,20,22,33]. Therefore, we measured the lysosomal pH in individual cells transfected with HB3-RFP and Dd2-RFP, compared with control cells transfected with RFP alone.…”
Section: Pfcrt Expression Caused Acidification Of the Ph In Lysosomesmentioning
confidence: 98%
“…To monitor hemoglobin uptake and parasite viability simultaneously we established a correlative flow cytometric assay employing parasites that had invaded resealed RBCs containing a fluorescent marker (21). The fluorescein-dextran was taken up into the parasite's digestive vacuole and used to monitor the level of endocytosis (green fluorescence intensity) following selective lysis of the RBC membrane by saponin (23).…”
Section: Resultsmentioning
confidence: 99%